Chronic effects of a static stretching intervention program on range of motion and tissue hardness in older adults - Nakamura, Masatoshi; Scardina, Antonino; Thomas, Ewan; Warneke, Konstantin; Konrad, Andreas (Frontiers in Medicine, 2024)
Clinically, knowing whether a static stretching (SS) intervention program conducted for several weeks can reduce passive muscle stiffness is important. Still, only a few previous studies have evaluated the chronic effects of an SS intervention program in older adults, and the potential relationship between ROM changes and muscle stiffness changes is still unclear. This study aimed to investigate the effects of a 10-week SS intervention partially supervised program on joint range of motion (ROM) and tissue hardness in older adults. The SS intervention program was conducted at least three times a week for 10 weeks in the ankle plantar flexor muscles of 24 community-dwelling older adults (73.8 ± 5.1 years; height: 156.0 ± 6.8 cm; body mass: 52.7 ± 8.0 kg). The SS intervention program consisted of 4 × 30s repetitions. Ankle joint dorsiflexion (DF) ROM and tissue hardness of the medial gastrocnemius were measured before and after the 10-week SS intervention program. The results showed that the 10-week SS intervention program significantly increased DF ROM (+9°, p<0.01, Cohen's d = 1.37) and decreased tissue hardness (-0.9, p=0.04, Cohen's d = -0.27). However, there was no significant correlation between these changes (r = 0.086, p = 0.561). The results of this study suggest that a 10week SS intervention program can effectively increase DF ROM and decrease tissue hardness but that the increase in DF ROM is related to stretch tolerance rather than changes in tissue hardness.